Paisajes y saberes - Mirás, Marta Liliana; Willemsen, Jorge Pablo; Fabio, Verónica; Kanai , Juan Miguel (Anales del Instituto de Arte Americano e Investigaciones Estéticas «Mario J. Buschiazzo», 2022)
Palabras clave: paisajismo, diseño del paisaje, historia urbana